Recent progress of blue fluorescent organic light-emitting diodes with narrow full width at half maximum. (December 2022) - Xie, Mingliang; Sun, Mizhen; Xue, Shanfeng; Yang, Wenjun
Abstract: Blue fluorescent emitters and devices are essential due to their unique advantages in realizing ultra-high-definition displays and reducing power consumption. Blue fluorescent emitters with narrow full width at half maximum (FWHM) emission spectra exhibit sufficient color purity to achieve ultra-high-definition displays with reduced power consumption. Much effort has been devoted to developing narrowband blue-emitting emitters and devices, and tremendous progress has been made over the past two decades. However, the reason for the narrowband emission of the emitters and the way to achieve the narrowband emission is unclear. Therefore, this work summarizes six types of emitters according to the reasons for inducing narrowband emission or/and the way to achieve narrowband emission and explores the relationship between the FWHM value of the emission spectrum of the emitter and the molecular structure or/and device structure. This work may inspire future researchers' enthusiasm for narrowband efficient blue emission research. Graphical abstract: This work summarizes six classes of emitters according to the reasons for inducing narrowband emission or/and the approach to achieving narrowband emission, obtains the relationship of emission spectrum FWHM to emitter structure, and demonstrates the approach to narrowband emission using advanced device technology. Image 1 Highlights: Six ways to realize narrowband emission are summarized. Blue emitters and device technologies to achieve narrowband emission are summarized. Design strategies for narrowband blue fluorescent emitters.